Socioemotional Resources and Mental Health in Moroccan Adolescents: A Person-Centered Approach - Pulido-Martos, Manuel; Cortés-Denia, Daniel; El Ghoudani, Karima; Luque-Reca, Octavio; Lopez-Zafra, Esther (Frontiers in Psychology, 2022)
Mixture modeling technics are not the one and only to perform person-centered analyses, but they do offer the possibility of integrating latent profiles into models of some complexity that include antecedents and results. When analyzing the contribution of socio-emotional resources to the preservation of mental health, it is the variable-centered approaches that are the most often performed, with few examples using a person-centered approach. Moreover, if the focus is on the Arab adolescent population, to our knowledge, there is an absence of such studies. This study aims to extends the research about socioemotional resources by examining: 1) if distinguishable profiles can be identified based on scores about perceptions of different emotional abilities and levels of social support from different sources (parents, friends and teachers/counsellors); 2) if the identified profiles relate to mental health indicators, such as depression levels and health-related quality of life; and 3) to acknowledge if sociodemographic variables such as age or gender and positive self-views (self-esteem) ascertain the probability of pertaining to the identified profiles. The study was carried out on a large sample of Moroccan adolescents (N = 970). We adopted a person-centered approach using latent profile analysis (LPA) to establish whether different socio-emotional resources (emotional intelligence and social support) profiles are present in Moroccan adolescents. Furthermore, we investigated the role of sociodemographic variables and self-esteem as antecedents of these profiles and the association of these profiles with mental health (depression and health-related quality of life). Results from LPA revealed three patterns of socioemotional resources (i.e., latent profiles): 1) “High socioemotional resources” (43.09%); 2) “Moderate socioemotional resources” (42.68%); and 3) “Low socioemotional resources” (14.23%). Analyses showed that Moroccan adolescents differed significantly in depression (cognitive-affective and somatic dimensions) and health-related quality of life depending on the profile membership. Profiles with higher levels of resources contributed positively to preserving mental health. Finally, the results show that self-esteem boosted the probability of pertaining to the profiles related to a better mental health. Thus, this study extends previous research about socioemotional resources, highlighting that researchers and health professionals should consider empirically identified profiles of adolescents when explaining mental health outcomes.